The Politics of Decolonial Investigations - Mignolo, Walter (Durham : Duke University Press, 2021)
"Walter D. Mignolo provides a sweeping examination of how coloniality has operated around the world in its myriad forms between the sixteenth and twenty-first centuries while calling for a decolonial politics that would delink from all forms of Western knowledge"--
Racism as we sense it today -- Islamophobia/Hispanophobia -- Dispensable and bare lives -- Decolonizing the nation-state -- The many faces of cosmo-polis -- Cosmopolitan and the decolonial option -- From "human" to "living" rights -- Decolonial reflections on hemispheric partitions -- Delinking, decoloniality, and de-Westernization -- The South of the North and the West of the East. -- Mariátegui and Gramsci in "Latin" America -- Sylvia Wynter : what does it mean to be human? -- Decoloniality and phenomenology -- The third nomos of the earth -- Epilogue: Yes, we can : border thinking, colonial epistemic/aesthesic differences and pluriversality.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Decolonization; Postcolonialism; Racism -- Political aspects; Knowledge, Theory of -- Political aspects; Civilization, Western; Civilization, Modern